KEBIJAKAN HUKUM PIDANA PERLINDUNGAN ANAK DALAM PEMBARUAN SISTEM PERADILAN PIDANA ANAK DI INDONESIA - Candra Hayatul Iman (Jurnal Hukum dan Peradilan, 2013)
Juvenile Delinquency is an anti-social behavior can be disturbing public society, but it is recognized as a common phenomenon that must be accepted as a social fact. Children based on their physical, mental and social have a weak position compared with adults, so that children who committed needs to be special treatment. Therefore, the treatment of juvenile delinquents should be different with the treatment of adults. Child Protection in fact there are still many who have not accommodate the principles of international instruments. In the juvenile court still found violations of children's rights in the implementation of the handling of children in conflict with the law. Research it can be concluded that the formulation of policies for the protection of children in conflict with the law in the juvenile justice system in Indonesia is regulated in Law No. 3 Year l997 on Juvenile Court has not accommodated the principle of the best interest of the child in the juvenile justice system, so it is normative in the formulation did not reflect the level of the basic idea of the protection of children. Thus, the level of normative formulation does not reflect the basic idea of the child protection law. Formulation studies to the protection of children in conflict with the law in the juvenile justice system in accordance with Law No. 11 Year 2012 has been to accommodate the principle of the best interest of the child with the diversion. Yet undiscovered principles of availability of legal aid in the context of the principle of diversion and diversion control authority. Formulation studies to the protection of children in conflict with the law in the juvenile justice system in accordance with Law No. 11 Year 2012 has been to accommodate the principle of the best interest of the child, among others, by focusing on the handling of children in conflict with the law through diversion measures to promote restorative justice approach. Application policy to the protection of children in conflict with the law in the juvenile justice system involves substantial problems, structural and cultural. Paradigm of retributive justice system is still an idea in Act No. 3 of 1997. Keywords: Criminal Law Policy; child protection, juvenile justice system reform.